Transformational leadership, self-efficacy, and work performance among lecturers in higher education institutions: conceptual analysis on a mediation model - Kang, Lulu; Abdul Aziz, Nor Azni; Che Hassan, Norlizah (Human Resource Management Academic Research Society, 2024)
The main objective of this study is to investigate the relationship between perceived transformational leadership and work performance based on social exchange theory in the context of higher education institutions. Meanwhile, the paper also aims to test the role of self-efficacy working as a mediating variable in this relationship, since the potential mediating mechanism has found its support in the theoretical context of social cognitive theory, where interaction and influence take place among environmental, personal, and behavioral elements. Thus, this study may offer a better understanding of the role played by personality traits such as self-efficacy in the influential path of transformational leadership toward work performance. The research findings from a different sample (lecturers) and context (higher education) will not only broaden the existing literature but also encourage future research initiatives on the topic.